2019
DOI: 10.1136/gutjnl-2019-319511
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns and trends in colorectal cancer incidence in young adults

Abstract: ObjectiveEarly-onset colorectal cancer (CRC) is increasing in the USA despite rapid declines in older ages. Similar patterns are reported in Australia and Canada, but a comprehensive global analysis of contemporary data is lacking.DesignWe extracted long-term data from Cancer Incidence in Five Continents and supplemental sources to report on worldwide CRC incidence rates and trends by age (20–49 years and ≥50 years) through diagnosis year 2012 or beyond (Australia, Finland, New Zealand, Norway, Sweden, USA).Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
417
2
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 553 publications
(504 citation statements)
references
References 57 publications
21
417
2
9
Order By: Relevance
“…Unlike most studies (Siegel et al, 2019), our study only showed a declining trend in the mortality but not in the incidence rates of CRC in the above-50 group. Moreover, in contrast to the previous findings (Fu et al, 2014), the older patients were not shown to have a lower mortality risk as compared with their younger counterparts.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike most studies (Siegel et al, 2019), our study only showed a declining trend in the mortality but not in the incidence rates of CRC in the above-50 group. Moreover, in contrast to the previous findings (Fu et al, 2014), the older patients were not shown to have a lower mortality risk as compared with their younger counterparts.…”
Section: Discussioncontrasting
confidence: 99%
“…Colorectal carcinoma (CRC) is the third most commonly diagnosed malignancy and the fourth cause of cancer-related death worldwide [1,2]. Recently, cancer registry data show that in some high-income countries an increasing incidence of CRC in adults younger than 50 years [3]. Changes in dietary patterns which is called as western lifestyle are considered to be high risk factors for CRC.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, until recently, data on CRC incidence among younger adults were lacking. The most recent studies show that, even though in most European countries the EOCRC incidence has risen, there is a wide spectrum of heterogeneity between countries [7,8]. During the most recent decade of available data, CRC incidence rates have uniquely increased in young adults in countries, such as Germany, the UK, Denmark, Slovenia, and Sweden, while conversely, CRC declined in young adults in only three countries (Italy, Austria and Lithuania); in Cyprus, the Netherlands, and Norway, inclines in the incidence in young adults were twice as rapid as those in older adults [7].…”
Section: Introductionmentioning
confidence: 99%